Human Resource Management in Broadcasting Organizations - Muchammad Ainur Rofiqi; Ikes Niswatul Bestari; M. Nauval Zhahfran Fauji; Nadya Latifatu Rohmah; Evi Fatu Sholiha; Faruq Faruq (IJIP : Indonesian Journal of Islamic Psychology, 2024)
Human Resource (HR) management is one of the most important factors in determining organizational success. One of them is a broadcasting organization. This research aims to identify the HR management process in broadcasting organizations and find implementation strategies. This type of research uses qualitative research methods with a phenomenological approach. This research uses purposive sampling data collection techniques with five participants at the SATU TV broadcasting organization with the following characteristics: first, the participant must be an organizer and currently serving in one of the broadcasting organizations, the second must have experience in being a producer or in leading the program, on the organization. The data collection instrument used was interviewed. The research results reveal the process of HR management in broadcasting organizations as follows: 1) division of tasks and authority, 2) becoming a forum for talents and interests, 3) established communication, 4) HR development, and 5) evaluation. The strategies carried out in the management process are as follows: 1) there are challenges to finding solutions for, 2) approach the crew, 3) overcome boredom with holidays, and 4) empower seniors in the production process if they experience difficulties. The results of this research can help organizational producers in the broadcasting sector manage HR.